2016
DOI: 10.1177/0961203316657433
|View full text |Cite
|
Sign up to set email alerts
|

Persistent triple antiphospholipid antibody positivity as a strong risk factor of first thrombosis, in a long-term follow-up study of patients without history of thrombosis or obstetrical morbidity

Abstract: Introduction The long-term risk of first thrombosis and benefit of prophylaxis in antiphospholipid antibody (aPL) carriers without history of thrombosis or obstetrical morbidity is poorly known. This study aimed to evaluate the long-term rate and risk factors associated with a first thrombosis in those patients. Patients and methods After a prior study ended in December 2005 and was already published, we extended the follow-up period of our cohort of aPL carriers. Results Ninety-eight of the 103 patients of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 23 publications
3
39
0
Order By: Relevance
“…We observed no association between TP and the site of thrombosis or thrombosis recurrence. This finding was not expected because previous clinical studies have shown that TP confers higher risk for the development of thrombosis and recurrent thrombotic events . We believe that the risk of thrombosis in APS may not be attributed solely to the aPL profile.…”
Section: Discussionmentioning
confidence: 61%
“…We observed no association between TP and the site of thrombosis or thrombosis recurrence. This finding was not expected because previous clinical studies have shown that TP confers higher risk for the development of thrombosis and recurrent thrombotic events . We believe that the risk of thrombosis in APS may not be attributed solely to the aPL profile.…”
Section: Discussionmentioning
confidence: 61%
“…1 A recent long-term follow-up study reported persistence of aPL over time to be associated with the highest risk of thrombosis in triple-positive patients. 79 A retrospective study evaluated extended persistence and demonstrated persistence in 96% in a median follow-up of 56 weeks, with no significant lower persistence in the single positive patients compared with the double and triple positives. 80 These results support the choice of extending the retest interval beyond 12 weeks, which would identify patients who remain persistently positive even beyond this period.…”
Section: Confirmati On Of Per S Is Tent L a P Os Itivit Ymentioning
confidence: 99%
“…Contrary to this, aPLs' persistence was shown to increase the annual risk of thrombosis by up to 5%. The highest risk is observed in patients with so-called triple positivity, which refers to the state when all the three aPLs are present simultaneously (LA, aCL, and anti-β2GPI) [82].…”
Section: Antiphospholipid Syndromementioning
confidence: 99%